An Overview of the Potential Impact of the COVID-19 Crisis on the Accumulation of Government Expenditure Arrears - Utz, Robert; Mastruzzi, Massimo; Vazquez Ahued, Francisco; Tawfik, Ehab (World Bank, Washington, DC, 2021)
The Coronavirus (COVID-19) pandemic introduced tremendous fiscal pressures for many countries, requiring additional spending to mitigate the health, economic, and social impacts of the pandemic while government revenues are falling. Governments are addressing these fiscal pressures through a range of measures, including additional borrowing and expenditure adjustments. In environments where fiscal space is tight and public expenditure management is weak, the accumulation of government expenditure arrears is likely. This note presents some early data on the impact of these fiscal pressures on government arrears in low income countries.